UNVEILING THE CURTAIN: THE METAMORPHOSIS OF ITALIAN THEATRE IN THE 21st CENTURY THROUGH THE LENS OF GLORY WALL - Ioannidou, Victoria (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
Italian theatre in the 21st century has witnessed significant changes in the management of censorship and freedom of expression. This study explores the evolution of the Italian theatre landscape, focusing on the emblematic case of Glory wall, winner of the 2020 Theatre Biennale in Venice. Through an in-depth analysis of this case, we examine the transition from traditional censorship to its total absence in contemporary Italian theatre and the implications of this transformation for artists, audiences, and society as a whole. Additionally, we will reflect on the concept of total freedom of expression and the role of censorship in shaping the artistic landscape, as well as the phenomenon of self-censorship. As Paul Valéry famously said, «art lives on constraints and dies of freedom», underscoring the delicate balance between artistic constraints and creative freedom in the theatre.